Parasitoids of fl y collected in urban area in Brazil - Carlos Henrique Marchiori (Annals of Marine Science - Peertechz Publications, 2019)
Parasitoids are important regulators of insect populations and stand out as the main group of natural enemies in agricultural systems. They are present in various orders of insects and their adaptation to a parasitic behavior is seen most diversely and abundantly in the order Hymenoptera [1]. Another application of parasitoids may be related (besides biological control) to the study of Forensic Entomology which is the use of ecological data and development of necrophagous insect to estimate the postmortem interval in criminal investigations.